Draft Annual Plan 2008-2009 Volume-II (Tables) Government of Rajasthan - Planning Commission (Planning Commission, 2008)
Proposed Outlay - Major Heads / Minor Heads of Development Proposed Outlay - Major Heads / Minor Heads of Development - From State Budget Proposed Outlay - Major Heads / Minor Heads of Development - From Public Sector Enterprises Proposed Outlay - on Continuing and New Schemes Physical Targets and Achievements Statement regarding Externally Aided Projects Bharat Nirman Programmes Centrally Sponsored Schemes Tribal Sub-Plan (TSP-1) - Financial Outlays Scheduled Caste Sub-Plan (SCSP-1) - Financial Outlays.
Government of Rajasthan, Planning Department
Government of Rajasthan, Planning Department